Walkability of Bukit Bintang Commercial District, Malaysia - Salim, Atirah (2012)
The aim of this study is to measure the walkability of Bukit Bintang Commercial District and factors influencing it. The concern includes not only the urban design qualities that may promote walking such as well maintained and good pavement of walkway, but also the psychological aspect, such as the pleasure and enjoyment of walking. However, the provision of walking environment is mainly focused on fulfilling only the technical requirements and less on the quality of the environment. Inconsistency of streetscape elements and lack of clarity in the movement pattern are some of the problems identified in Jalan Bukit Bintang. The criteria and measurement is identified from theories and principles on walkable environment and reliable assessment format by good practices. Spatial Context; Urban Structure; Accessibility; Connectivity and Safety are identified as the main determining criteria for walkability in the context studied. In the measurement, field assessments were conducted by the researcher to evaluate the level of walkability. A survey was conducted with 330 respondents to obtain their perceptions towards the walkability of Bukit Bintang Commercial District according to the specified zones. The findings indicate that the walkability in Bukit Bintang Commercial District is generally at the medium level where it ables to meet some of the criteria needed to provide walkable environment which are urban structure and accessibility. Results from the perception survey indicate that safety and connectivity of the paths strongly influence the perceived comfort of walking by pedestrians. It is therefore important to improve on the safety and connectivity of the public spaces to increase the level of walkability in the area. The findings from this study will contribute to the identification of the factors that influence the walkability of Bukit Bintang Commercial District that can be utilized as a guideline to improve the existing condition of the area for the benefit of the pedestrian. The methods and techniques to access the walkability of Bukit Bintang Commercial District based on the established walkability assessment methods developed by PERS and Gallin can be referred to as a guide to assess other areas. In general, the findings of the study will strengthen the urban design theory and practice with regards to determining the walkability of compact urban commercial district in Malaysian cities.